2020
DOI: 10.1556/2006.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and Internet gaming disorder: The role of motives and metacognitions

Abstract: Background and aimsIn recent years, Internet Gaming Disorder (IGD) has been recognized as a mental health problem. Although research has found that social anxiety, motives, the preference for online social interactions (POSI), and metacognitions about online gaming are independent predictors of IGD, less is known about their relative contribution to IGD. The aim of the current study was to model the relationship between social anxiety, motives, POSI, metacognitions about online gaming, and IGD.MethodsFive hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 62 publications
9
50
0
1
Order By: Relevance
“…The goal of the present study was to examine personality correlates of gaming and pornography use to discern similarities and differences in these two problematic internet use behaviors. In partial support of hypothesis one and consistent with previous research, we found anxiety (e.g., Marino et al, 2020) and impulsivity (Hu et al, 2017;Kuss & Griffiths, 2012) to have a significant positive correlation with gaming use. It may be that as individuals become more anxious and impulsive, their gaming behaviors become more prevalent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The goal of the present study was to examine personality correlates of gaming and pornography use to discern similarities and differences in these two problematic internet use behaviors. In partial support of hypothesis one and consistent with previous research, we found anxiety (e.g., Marino et al, 2020) and impulsivity (Hu et al, 2017;Kuss & Griffiths, 2012) to have a significant positive correlation with gaming use. It may be that as individuals become more anxious and impulsive, their gaming behaviors become more prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…use behaviors (Lee & Stapinski, 2012). Specifically, several studies found that anxiety is positively associated with IGD (Adams et al, 2019;Bargeron & Hormes, 2017;Bonnaire & Baptista, 2019;Marino et al, 2020;Wang et al, 2017) as well as PPU (Niazof et al, 2019;Shirk et al, 2021). Trait anxiety is defined as a relatively stable state of proneness to experiencing anxiety (Julian, 2011).…”
mentioning
confidence: 99%
“…34 Social anxiety has also been found to impact on IGD through motives and metacognitions of online social interactions. 39 Moreover, FoMO may also stimulate impulsive consumption in marketing and communication activities because of fearing of missing out on something. 40 Kim et al 41 also reported that FoMO was an extrinsic motivation (e.g., ''It's a big game not to miss out'') that may promote popular sport event consumption (e.g., Olympics, FIFA World Cup, and the Super Bowl).…”
Section: Introductionmentioning
confidence: 99%
“…Several psychiatric conditions, such as impulsiveness, depression, social anxiety, obsessive-compulsive disorder (OCD), and autism spectrum disorder (ASD) have been more frequently associated with the presence of IGD [ 8 , 9 , 10 ]. Other authors showed strong association of IGD with Hikikomori Syndrome, a severe form of social withdrawal, suggesting bidirectional interactions between these two conditions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies in this field did not clarify if IGD should be considered, with respect to the other disorders in comorbidity, as a predisposing factor, as a consequence, or simply as a co-occurring condition. In this latter case, it is possible that IGD would share some vulnerability factors with other kinds of mental disorders [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%